2005
DOI: 10.1007/s11250-005-9002-5
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Factors Affecting the Survival of Donkeys in Semi-arid Regions of Sub-Saharan Africa

Abstract: The large fluctuations seen in cattle populations during periods of drought in sub-Saharan Africa are not evident in the donkey population. Donkeys appear to have a survival advantage over cattle that is increasingly recognized by smallholder farmers in their selection of working animals. The donkey's survival advantages arise from both socioeconomic and biological factors. Socioeconomic factors include the maintenance of a low sustainable population of donkeys owing to their single-purpose role and their low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 32 publications
(41 reference statements)
1
45
0
1
Order By: Relevance
“…Today donkeys are essential means of transport for people living in many mountainous, desert and poor regions of the world [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Today donkeys are essential means of transport for people living in many mountainous, desert and poor regions of the world [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been undertaken to evaluate husbandry and welfare aspects of working equids, either used in farming systems or urban activities, in arid or semi-arid countries (Smith and Pearson 2003, Kay et al 2004, Pritchard et al 2005, Pearson and Krecek 2006. Only a few studies regarding draught horses have been undertaken in countries like Chile that have a rainy temperate climate with a Mediterranean influence in the south (Meyer 1992, Tadich et al 1997, 2007.…”
mentioning
confidence: 99%
“…and environmental factors, no studies were found. If many references concerning the effects of heat stress on the nutritional composition of dairy species milk, are available [27,28], when referring to donkey colostrum, a notable scarcity of data may be noticed.…”
Section: Resultsmentioning
confidence: 99%